The Clinical Efficacy and Applications of Portable Imaging Devices in Emergency Medical Settings: A Comprehensive Review - Alqozi , Amnah Ahmad Yahya; Almutairi, Rayhanah Saud Saad; Alharbi, Barjas Fahad; Jubran, Yahya Nasser; ALYAHYA, MAJED IBRAHIM SAAD; Alsharidah, Ali Saad Abdullah; Alanazi, Sultan Marji; Alsahli, Mohammed Abdullah; Alsahli, Mohammed Atiah Atiahallah; Bohmail, Noof Mohammed; Shajiri, Mohammed Hamad Ali; Altayyar, Ahlam Mhommed; et al. (Journal of Ecohumanism, 2024)
Background: The integration of portable imaging devices in emergency medical settings has gained attention due to their potential to enhance diagnostic efficiency and facilitate timely patient care. Initial advancements in mobile imaging technologies under the Digital Imaging and Communications in Medicine (DICOM) standard date back to 2003, yet their clinical adoption remains limited. Methods: This review synthesizes findings from various studies sourced from prominent medical databases, including PubMed, Wiley Online Library, Web of Science, and Scopus. Key search phrases related to mobile DICOM viewers were employed to gather relevant literature assessing the diagnostic efficacy of mobile devices in interpreting radiological images in emergency scenarios. Results: Several studies highlighted that mobile device, including tablets and smartphones, can effectively display and interpret radiological images, offering diagnostic capabilities comparable to traditional PACS workstations. For instance, mobile applications significantly reduced consultation times and enhanced accessibility to imaging data. However, the European Society of Radiology cautioned against their use for primary interpretations, recommending them instead for supplementary opinions or bedside evaluations. Conclusion: The findings underscore the feasibility of utilizing portable imaging devices in emergency settings to improve access to diagnostic imaging and expedite clinical decision-making. Despite their advantages, ongoing concerns regarding image quality, usability, and the need for robust IT infrastructure must be addressed to facilitate broader adoption in clinical practice.